Can local 5G networks using local spectrum be used as platform for digitalization of industrial systems and services? - Jan Markendahl; Claes Beckman (International Telecommunications Society (ITS), 2022)
Local 5G spectrum licenses has recently attracted a great deal of attention and expectations from both industry and governments all over the world. One reason is the expectation that 5G local industrial networks using local spectrum can be used to support digitalization of industrial processes, and hence increase productivity of industrial use cases. In support of these expectations, governments all over the world have allocated spectrum for local 5G licensing in the 3.5GHz band with various conditions. This paper focuses on local 5G networks for "private" use, these non-public networks are commonly referred to as Non-Public Networks (NPNs). We present results and discussion about implications in three areas: 1. Network capacity and cost for 5G NPN for industrial use - 2. Allocation of local spectrum licenses - 3. Ecosystem analysis of business models and value networks. For the two first areas our analysis indicates that previously identified questions related to radio-interference and co-existence between NPN and operator macro cell networks still seem to be challenging. It is unclear if 5G NPN using Time-Division Duplex (TDD) at the 3.5 GHz band can satisfy performance and operational needs in the field of industrial radio systems. Hence, the value of this type of local 5G licenses need to be further discussed. For the third area and the question "what actor is doing what?" we see a need to look more into solutions where different types of actors cooperate and contribute to different parts of the value network. This is in contrast to what is described in many papers and reports where the assumption is that one type of actor will take care of all or most of the roles.
Keywords: 330